Tracking gender equity under economic reforms continuity and change in South Asia - Mukhopadhyay, Swapna; Sudarshan, Ratna M.; International Development Research Centre (Canada); ProQuest (Firm) (Ottawa : International Development Research Centre ; New Delhi : Kali for Women, 2003)
Contributed articles on women employees in economic development process in South Asia.
Non-conventional indicators of gender disparities under structural reforms / Shobna Sonpar and Ravi Kapur -- Household response to gender issues : a survey on households of female EPZ workers in Bangladesh / Salma Chaudhuri Zohir -- Status of women under economic reforms : the Indian case / Swapna Mukhopadhyay -- Economic reform and the status of women in Nepal / APROSC -- Gender and adjustment policies : evidence from Pakistan / Rehana Siddiqui, Shahnaz Hamid, Rizwana Siddiqui, and Naeem Akhtar -- Continuity and change : women workers in garment and textile industries in Sri Lanka / Swarna Jayaweera -- Family structure, women's education and work : re-examining the high status of women in Kerala / Mridul Eapen and Praveena Kodoth -- Trade, gender, and employment issues / Manju Senapaty -- Gender in a macroeconomic framework : a CGE model analysis / Anushree Sinha and Sangeeta N. -- Towards integration? gender and economic policy / Ratna M. Sudarshan.
Includes bibliographical references.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Women in economic development -- South Asia; Women employees -- South Asia -- Economic conditions; South Asia -- Economic conditions; Electronic books